Pleomorphic adenoma of the hard palate in a 61-year-old patient - Chiżyński, Adam; Osica, Piotr; Stelmach, Rafał; Janas-Naze, Anna (Journal of Education, Health and Sport, 2017)
The article describes a case of pleomorphic adenoma in a 61-year-old patient, its diagnostic methods and treatment.